Reversal of IKZF1-induced glucocorticoid resistance by dual targeting of AKT and ERK signaling pathways - Butler, Miriam; Vervoort, Britt M.T.; van Ingen Schenau, Dorette S.; Jongeneel, Lieneke; van der Zwet, Jordy C.G.; Marke, René; Meijerink, Jules P.P.; Scheijen, Blanca; van der Meer, Laurens T.; van Leeuwen, Frank N. (Frontiers in Oncology, 2022)
Although long-term survival in pediatric acute lymphoblastic leukemia (ALL) currently exceeds 90%, some subgroups, defined by specific genomic aberrations, respond poorly to treatment. We previously reported that leukemias harboring deletions or mutations affecting the B-cell transcription factor IKZF1 exhibit a tumor cell intrinsic resistance to glucocorticoids (GCs), one of the cornerstone drugs used in the treatment of ALL. Here, we identified increased activation of both AKT and ERK signaling pathways as drivers of GC resistance in IKZF1-deficient leukemic cells. Indeed, combined pharmacological inhibition of AKT and ERK signaling effectively reversed GC resistance in IKZF1-deficient leukemias. As inhibitors for both pathways are under clinical inve¬¬stigation, their combined use may enhance the efficacy of prednisolone-based therapy in this high-risk patient group.